Timing of gamma irradiation and blood donor sex influences in vitro characteristics of red blood cells. Issue 4 (17th January 2018) - de Korte, Dirk; Thibault, Louis; Handke, Wiebke; Harm, Sarah K.; Morrison, Alex; Fitzpatrick, Aine; Marks, Denese C.; Yi, Qi‐Long; Acker, Jason P.; ,
Abstract : BACKGROUND: There are few studies investigating the effect of irradiation on red blood cells (RBCs) during storage. This study analyzed changes in in vitro quality of RBCs irradiated at several points during storage with the aim of providing evidence to support current maximum pre‐ and postirradiation storage limits. STUDY DESIGN AND METHODS: Each of seven participating centers produced four pools of 7 standard RBC units (SAGM, AS‐3, or PAGGSM), which were then split back into 7 units. All units in a pool were from sex‐matched blood donors. Every week during 6 weeks of refrigerated storage, 1 unit was irradiated, while 1 unit was not irradiated (control). Units were tested weekly for biochemical variables, morphology, and mechanical fragility. RESULTS: The earlier during storage that units were irradiated, the higher the hemolysis and K + at end of storage. Irrespective of the timing of irradiation, there was a rapid increase in extracellular K +, followed by a more gradual increase in hemolysis. ATP levels decreased faster in irradiated units and were reduced below accepted values if irradiated early. Irradiated female RBCs had an absolute lower hemolysis and K + level compared to male RBCs at all time points. CONCLUSIONS: The method of blood component manufacturing determined the absolute levels of hemolysis and potassium in irradiated and nonirradiated units, but did not influence the effect that timing of irradiation had on the in vitro quality characteristics. This study provides support for the current Council of Europe guidelines on the time limitations for the irradiation of RBCs.